PENDEKATAN KOMPREHENSIF GERIATRIK PADA PASIEN LANSIA DENGAN HERNIA NUKLEUS PULPOSUS LUMBAL - Andira Larasari; Muhamad Fakhri Arsyad; Baitya Ananda Surya Zahira; Muhammad Arief Candrasalim; Hamda Hamda; Cecilia Esther Ivena; Alvia Cahya Puteri Susanto; Agnes Tineke Waney Rorong; Andini Aswar; Michelle Sugandi (Jurnal Akta Trimedika, 2026)
Herniated nucleus pulposus (HNP) is a common cause of low back pain in older adults, leading to decreased quality of life and independence. This condition is often accompanied by multimorbidity, requiring a comprehensive geriatric approach for diagnosis and management. A 69-year-old female presented with chronic low back pain for three years, aggravated by prolonged sitting, and accompanied by numbness in the right leg. Her medical history included left-sided gonarthrosis post-surgery, cataract, hypertension, and diabetes mellitus. MRI revealed a disc herniation at the L4–L5 segment. Comprehensive geriatric assessment showed mild dependency, low functional capacity, suspected depression, risk of malnutrition, and frailty. A multidisciplinary conservative approach was implemented, including analgesic therapy, posture education, activity modification, nutritional optimization, and family support. This case highlights the importance of multidimensional evaluation in elderly patients with HNP, as successful management depends not only on pain control but also on addressing comorbidities, psychosocial factors, and functional status to prevent disability and improve quality of life.